Shelf Life Estimation of Taro Flour Packaged in Polypropylene (PP) and High-Density Polyethylene (HDPE) Using The Arrhenius Approach - Shafira Pradyta; Dyah Wulandani; Rokhani Hasbullah (The University of Lampung, 2025)
Taro flour stored for an extended period tends to experience a decline in quality. Therefore, determining the optimum storage period is essential. The Accelerated Shelf Life Testing (ASLT) method using the Arrhenius model was applied to estimate the shelf life of taro flour. The research on taro flour was carried out in three stages. The first stage involved the production of taro flour. The second stage included monitoring changes in quality during the storage period. The third stage focused on estimating the shelf life of taro flour packaged in polypropylene (PP) and high-density polyethylene (HDPE) materials. Drying and milling taro tubers produced taro flour with a final moisture content of 10%. During the storage period, observations were made on moisture content, whiteness degree, and protein content. Shelf life estimation was conducted using the Arrhenius model, with the selection based on a critical quality parameter protein content. The results indicated that the estimated shelf life of taro flour based on protein content in PP and HDPE packaging at 25 ℃ was 223 days and 285 days, respectively. Meanwhile, at storage temperature of 28 ℃, the shelf life of taro flour in PP and HDPE packaging was estimated to be 147 days and 183 days, respectively.